JUSTICE AND THE RULE OF LAW ARE THE MAIN AND NECESSARY CONDITION FOR THE DEVELOPMENT OF SOCIETY - Abdullayeva Asila (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
this scientific article describes in detail about the judicial and legal systems that are being carried out at the present time. As such, the rule of law has been brought.